The Effectiveness Of Using Cubing Strategy In Writing Descriptive Text - Eka Agustina; Nilawati Munawwaroh; Dian Wijayanti; Ajeng Oktaviana; Heni Erlinawati (Journal on Education, 2024)
This study is titled "The effectiveness of using cubing strategy in writing descriptive text". The purpose of this study is to find out whether there is a significant effect between thinking students using the cubing strategy and non-thinking students using cubing strategy in teaching descriptive writing to students. MTS 8th grade student Raudhatul istiqomah lirboyo suroboyo or not.therefore, this study is quantitative, using experimental methods and quasi-experimental design. The sampling technique was chosen according to the purposive sampling method. There are two groups: the experimental group (VIIIA) with 31 students and the control group (VIIIB) with 31 students. In this study, the author used several codes as data collection tools. Based on the calculation performed by independent testing, the researcher found that the obtained result was larger (3092 > 2000) at the α = 0.05 significance level in the two-tailed test. This means that there was a significant effect between the experimental group and the control group. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that the block building strategy has been effective in teaching descriptive writing